Relationship Between Neutrophil-to-Lymphocyte Ratio (NLR) and Sepsis and Mortality in Patients Admitted to the Emergency Department: A Retrospective Observational Study - Boğa, Dr. Erkan (Eastern Journal of Medical Sciences, 2025)
Objective: This study aims to investigate the relationship between the neutrophil-to-lymphocyte ratio (NLR) and the diagnosis of sepsis and in-hospital mortality in patients admitted to the emergency department. Methods: This was a retrospective observational study conducted at the Emergency Department of Esenyurt Necmi Kadıoğlu State Hospital. Data from adult patients who presented to the emergency department between January 1, 2023, and December 31, 2024, were analyzed. Patients with complete blood count (CBC) results and suspected or confirmed infection were included. NLR values were calculated and compared between patients with and without sepsis, as well as between survivors and non-survivors. Multivariate logistic regression and ROC curve analysis were used to assess the predictive value of NLR for sepsis and mortality. Results: A total of 500 patients were included. Of these, 28.8% had sepsis, and 13.8% died during hospitalization. The mean NLR was significantly higher in patients with sepsis (6.4 ± 3.2) than in those without (3.9 ± 2.1) (p < 0.001), and non-survivors (7.2 ± 3.5) compared to survivors (4.5 ± 2.4) (p < 0.001). NLR was found to be an independent predictor of both sepsis (OR: 1.85, 95% CI: 1.42–2.41) and mortality (OR: 2.12, 95% CI: 1.55–2.91). The optimal NLR cutoff was 5.1 for sepsis and 6.8 for mortality. The AUC for sepsis and mortality prediction was 0.78 and 0.81, respectively. Conclusion: NLR is a simple, fast, and cost-effective biomarker that can aid in the diagnosis of sepsis and the prediction of in-hospital mortality in emergency department patients. Its routine use in clinical practice could enhance early detection and risk stratification, particularly in resource-limited settings.